2004
DOI: 10.1186/1477-9560-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of venous thromboprophylaxis and adherence to guideline recommendations: a cross-sectional study

Abstract: Background: Consensus Conferences and Guidelines for deep vein thrombosis prophylaxis have been published, which recommend the use of prophylactic heparins in patients with risk of venous thromboembolism (VTE). The aim of this study was the assessment of the prophylaxis of VTE and the adherence to accepted guideline recommendations throughout the hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…In several studies, prophylactic therapy showed 13-79% compliance with the standard treatment guidelines [1,4,10,12,17,18]. The results of the present study showed 83.3% compliance with ACCP guidelines.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…In several studies, prophylactic therapy showed 13-79% compliance with the standard treatment guidelines [1,4,10,12,17,18]. The results of the present study showed 83.3% compliance with ACCP guidelines.…”
Section: Discussionsupporting
confidence: 68%
“…Appropriate prophylaxis management can reduce the cost of treatment, duration of hospital stay, and the rate of side effects [6,10]. Despite the existence of many different guidelines, adequate thromboprophylaxis is not being correctly prescribed: high-risk patients are under-treated and low-risk patients are over-treated [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations